Solving Rational and Radical Equations: Mastery Test
Arrange the steps to solve the equation v1+3-V2r-1=-2.
Simplify to obtain the final radical term on one side of the equation.
Raise both sides of the equation to the power of 2.
Apply the Zero Product Rule.
Use the quadratic formula to find the values of x.
Simplify to get a quadratic equation.
Raise both sides of the equation to the power of 2 again plato​

Solving Rational and Radical Equations Mastery TestArrange the steps to solve the equation v13V2r12Simplify to obtain the final radical term on one side of the class=

Respuesta :

frika

Answer:

1 step: Raise both sides of the equation to the power of 2.

2 step: Simplify to obtain the final radical term on one side of the equation.

3 step: Raise both sides of the equation to the power of 2 again.

4 step: Simplify to get a quadratic equation.

5 step: Use the quadratic formula to find the values of x.

6 step: Apply the Zero Product Rule.

Step-by-step explanation:

Given the equation

[tex]\sqrt{x+3}-\sqrt{2x-1}=-2[/tex]

1 step: Raise both sides of the equation to the power of 2.

[tex](\sqrt{x+3}-\sqrt{2x-1})^2=(-2)^2\\ \\(\sqrt{x+3})^2-2\sqrt{x+3}\sqrt{2x-1}+(\sqrt{2x-1})^2=4\\ \\x+3-2\sqrt{x+3}\sqrt{2x-1}+2x-1=4[/tex]

2 step: Simplify to obtain the final radical term on one side of the equation.

[tex]x+3-2\sqrt{x+3}\sqrt{2x-1}+2x-1=4\\ \\3x+2-2\sqrt{x+3}\sqrt{2x-1}=4\\ \\-2\sqrt{x+3}\sqrt{2x-1}=4-3x-2\\ \\-2\sqrt{x+3}\sqrt{2x-1}=2-3x[/tex]

3 step: Raise both sides of the equation to the power of 2 again.

[tex](-2\sqrt{x+3}\sqrt{2x-1})^2=(2-3x)^2\\ \\4(x+3)(2x-1)=(2-3x)^2[/tex]

4 step: Simplify to get a quadratic equation.

[tex]4(2x^2-x+6x-3)=2^2-2\cdot 2\cdot 3x+(3x)^2\\ \\8x^2-4x+24x-12=4-12x+9x^2\\ \\8x^2+20x-12-4+12x-9x^2=0\\ \\-x^2+32x-16=0\\ \\x^2-32x+16=0[/tex]

5 step: Use the quadratic formula to find the values of x.

[tex]D=(-32)^2-4\cdot 1\cdot 16=1,024-64=960\\ \\x_{1,2}=\dfrac{-(-32)\pm \sqrt{960}}{2\cdot 1}=\dfrac{32\pm 8\sqrt{15}}{2}=16\pm 4\sqrt{15}[/tex]

Then the equation is

[tex](x-16-4\sqrt{15})(x-16+4\sqrt{15})=0[/tex]

6 step: Apply the Zero Product Rule.

[tex](x-16-4\sqrt{15})(x-16+4\sqrt{15})=0\\ \\x-16-4\sqrt{15}=0\text{ or }x-16+4\sqrt{15}=0\\ \\x_1=16+4\sqrt{15}\text{ or }x_2=16-4\sqrt{15}[/tex]